A Development of Social Engineer Skills Indicators for Students’ Udon Thani Rajabhat University - Deenang, Exkarach; Thanyasunthornsakun, Khanisara; Paisan, Teeraporn (Interdisciplinary Academic and Research Journal, 2023)
Udon Thani Rajabhat University create a new methodology of learning experience management beyond classroom by incubate the soft skill for their students through the process of social engineering, for the reflect achievements of this it necessary to data from instrumental containing indicators that can show offer characteristic individual. The purposes of this research were to develop of the social engineer skills indicators and to test of the goodness of fit of the structural model of social engineer skills indicators with empirical data. The method of research was divided into two phases, firstly, to synthesize the literature that related for build a indicators framework for validity test in the content area, secondly, to testing of the consistency of the model with empirical data. The sample was 121 undergraduates in UDRU Youth of Challenge and Change project. The research instruments were a four-level rating scale questionnaire has a content validity between of 0.80 to 1.00 and reliability 0.730. The statistic used for data analyze comprising of mean, standard deviation and confirmatory factor analysis. The research results were as follows; 1) the indicators social engineer skills of students’ Udon Thani Rajabhat university consisted of 4 skills and 20 indicators, in accordance to related principles, perspective and theories 2) the model of social engineer skills has a good consistency with the empirical data (X2/df = 2.940, GFI = 0.910, AGFI = 0.900, CFI = 1, SRMR = 0.018 and RMSEA < 0.001). Therefore, the social engineer skill component indicator has an appropriate component structure, can be used to develop the instrumental for assess social engineer skills of Udon Thani Rajabhat University students.